Developing Children's Sprituality Education - Hepni; Riayatul Husnan; Ahmad Khuza'i Faruq (State Islamic Institute of Madura, 2022)
A smart, intelligent, and skilled child is the desire of every parent. Therefore, not a few parents make various efforts so that their children can be smart in accordance with their expectations. This paper aims to reveal how great the desire of parents to make their children as desired, often experience some fundamental errors of orientation that actually destroy the future of their own children. The research method used is a qualitative approach with the type of library research. The results of the discussion show that the potential of children who are only focused on the Intelligence Quotient aspect will give birth to the child's personality which in fact becomes a Split Personality, Intelligence Quotient, therefore all three aspects must be developed equally.